2013
DOI: 10.1074/jbc.m113.466656
|View full text |Cite
|
Sign up to set email alerts
|

Cell Survival during Complete Nutrient Deprivation Depends on Lipid Droplet-fueled β-Oxidation of Fatty Acids

Abstract: Background: Cellular stress leading to cell death induces the formation of lipid droplets. Results: Nutrient deprivation induces LD biogenesis and mobilization, fueling fatty acid oxidation to sustain cell viability. Conclusion: ␤-Oxidation requires biogenesis and mobilization of LD. Significance: The role of LD in cell survival and ␤-oxidation might provide new potential targets for antitumor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
140
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 55 publications
8
140
0
1
Order By: Relevance
“…Our results show that pyrrolidine-2 pre-treatment dramatically increased the effectiveness of curcumin in U251N cells after 72 h, virtually abolishing cell viability at curcumin concentrations above 20 lM. Interestingly, the lipid droplet number of cells treated with curcumin following pyrrolidine-2 sensitization was higher than that of cells treated with curcumin alone -likely due to the drug-induced cellular stress, previously reported to induce lipid droplet formation [19,69,70]. Sensitization using BSO was comparatively less effective, likely due to the diversity of antioxidants and enzymes that can reduce ROS levels.…”
Section: Discussionmentioning
confidence: 63%
“…Our results show that pyrrolidine-2 pre-treatment dramatically increased the effectiveness of curcumin in U251N cells after 72 h, virtually abolishing cell viability at curcumin concentrations above 20 lM. Interestingly, the lipid droplet number of cells treated with curcumin following pyrrolidine-2 sensitization was higher than that of cells treated with curcumin alone -likely due to the drug-induced cellular stress, previously reported to induce lipid droplet formation [19,69,70]. Sensitization using BSO was comparatively less effective, likely due to the diversity of antioxidants and enzymes that can reduce ROS levels.…”
Section: Discussionmentioning
confidence: 63%
“…However, emerging evidences suggest that cancer cells can also rely on lipolytic pathways to use, when needed, stored lipids to acquire FFAs (39). In this regard, it has been demonstrated that FFAs liberated from lipid droplets are efficiently used to cope with the energy demand of nutritionally stressed cells (40). Concomitant TG synthesis and hydrolysis, such as observed in our study, has been described in both normal and pathological conditions (41)(42)(43).…”
Section: Discussionmentioning
confidence: 65%
“…Biophysical determinations have unveiled that accumulation of lysophospholipids with a wedge shape conformation such as lysoPC, lysoPE and, especially, lysoPA, generates a local positive membrane curvature, beneficial in terms of nascent LD budding [4,15,19,58,[64][65][66]. Since lysophospholipids are generated by PLA 2 s, the key role that cPLA 2 α appears to play in these stages of LD formation can be easily explained [21,46,[52][53][54] (Fig. 1).…”
Section: Mechanisms Of Ld Biogenesis Involving Cpla 2 αmentioning
confidence: 95%
“…From being regarded as mere storage depots for metabolic fuel and membrane-building blocks, LDs are now recognized as key players in the cellular regulation of lipid homeostasis, signaling, protein sorting, extra-and intracellular trafficking, and gene transcription regulation [15,19,20]. Furthermore, the formation of LDs may also constitute a sign of stress and of apoptotic cell death [21]. …”
Section: Introductionmentioning
confidence: 99%